Continuous Assessment Practice towards Students'Mathematics Prodiciency: THe Case of First-Cycle Primary Schools in Dire Dawa, Ethiopia - Fasil Girmay; Mulugeta Woldemichael (University of Sofia, 2022)
This study was conducted in three phases taking the case of 10 first-cycle primary schools at Dire Dawa, in Ethiopia. In phase I, qualitative base line survey was conducted in the selected schools for a month. In phase II, 40 teachers participated in one-day seminar on the formative assessment use, and then they co-designed assessment tasks and rubrics on mathematics proficiency spectrum in three workshops for two weeks. In phase III, continuous assessment implementation was studied in the selected schools to describe the extent to which instruction and assessment constructively aligned towards mathematics proficiency based on classrooms observations, semi-structured interviews and content analysis of assessment tasks for three months. Additionally, a closed ended questionnaire instrument was administered to examine teachers assessment practice. The findings of this study suggested primary teachers need close follow up and support rather than requesting them just to implement continuous assessments for developing students mathematics proficiency.